Adaptation of interdisciplinary clinical practice guidelines to palliative care for patients with heart failure in iran: application of adapte method - Imane Bagheri; Hojatollah Yousefi; Masoud Bahrami; Davood Shafie (Wolters Kluwer Medknow Publications, 2023)
Background: Clinical Practice Guidelines (CPGs) have been recommended to manage palliative care and take the best treatment measures and decisions. This study aimed to adapt the interdisciplinary CPG to provide palliative care for patients with Heart Failure (HF) in Iran based on the ADAPTE method. Materials and Methods: Guideline databases and websites were systematically searched up to April 2021 to determine appropriate publications related to the study topic. Followed by assessing the quality of the selected guidelines via the Appraisal of Guidelines for Research & Evaluation Instrument (AGREE II), those with appropriate standard scores were selected to be used in designing the initial draft of the adapted guideline. The developed draft contained 130 recommendations and was evaluated by a panel of interdisciplinary experts in terms of its relatedness, comprehensibility, usefulness, and feasibility in two phases of Delphi. Results: In the first phase of Delphi, the adapted guideline was derived from five guidelines and evaluated by 27 interdisciplinary pundits working in the universities of Tehran, Isfahan, and Yazd cities. After the assessment in Delphi Phase 2, four recommendation categories were removed because they did not receive the required scores. Finally, 126 recommendation items were included in the developed guideline, which were classified into three main categories of palliative care features, essentials, and organization. Conclusions: In the present study, an interprofessional guideline was designed to enhance palliative care information and practice in patients with HF. This guideline can be administered as a valid tool for interprofessional team members to provide palliative care to patients with HF.